Validity and Reliability of the Farsi Version of the Death Anxiety Scale With Nurses. (October 2021) - Dadfar, Mahboubeh; Lester, David; Abdel-Khalek, Ahmed M.
This study was conducted to determine the validity and reliability of Death Anxiety Scale (DAS), a scale designed by Templer to (1970) to assess the death anxiety, a scale which has been used extensively for research. A convenience sample of 106 Iranian nurses from two hospitals at Tehran city, Iran, was recruited. They completed the DAS, Death Concern Scale, the Collett-Lester Fear of Death Scale, the Reasons for Death Fear Scale, the Death Obsession Scale, and the Death Depression Scale. Cronbach's α, split-half, and 2-week test–retest reliabilities for the DAS were .60, .52, and .63, respectively. The DAS correlated .52, .38, .50, .47, and .50 with the aforementioned scales, respectively ( p < .01 level), indicating moderate validity. Principle components analysis of the DAS identified four factors: F1 "Death anxiety, " F2 "Fear of the future, " F3 Time passing, " and F4 "Thoughts of death." The DAS has only moderate validity and reliability. The DAS is brief (only 15 items) and may be useful for screening nurses and other hospital personnel for high death anxiety. Those with high scores may be better prepared for working with severely ill and dying patients after referring them for education and counseling.